Fracture pattern and failure mechanism of sandstone impacted by a high-pressure water jet under different stress loading states - Xiao, Songqiang; Xiao, Juchong; Ren, Qingyang; Feng, Renjun; Meng, Xin; Li, Wentao; Cheng, Yugang; Zhang, Wenfeng; Zhang, Liang; He, Junbo (Engineering fracture mechanics, 2025)
•Fragmentation characteristic of sandstone impacted by water jet under various stress loadings were studied.•A destructive-damage factor was introduced to quantify stress loading effects on rock breakage.•Stress and damage evolution inner rock under various stress loadings were analyzed.•Fracture patterns of sandstone impacted by water jet under stress loadings were revealed. High-pressure water jet technology is widely recognized as an efficient method for rock fragmentation in underground energy development and tunnel excavation engineering. The stress conditions of rock significantly influence the characteristics and efficiency of water jet breaking rock breakage. This study combines experimental and numerical simulation approaches to investigate the fracture patterns and failure mechanisms of rock subjected to water jet impact under various stress loading states. Through rock-breaking experiments, the effects of stress loading state, jet pressure, and rock lithology on the fragmentation characteristics and efficiency of sandstone were systematically examined. Utilizing a smoothed particle hydrodynamics-finite element method coupled algorithm, the evolution laws of damage and stress within the rock were quantitatively analyzed by introducing the comprehensive destructive-damage factor (Fcdd). Furthermore, the mechanisms underlying different fracture patterns and characteristics of sandstone fragmentation under varying stress loading states were elucidated. The results demonstrate that as stress loading increases, the threshold pressure for rock fragmentation rises, while rock-breaking efficiency decreases. Both rock-breaking depth and volume exhibit distinct trends with increasing jet pressure, following an S-shaped and exponential relationship, respectively. The unilateral stress loading is beneficial for the rock fragmentation and damage, with a more serious damage in stress loading direction, which is conducive to splitting fracture. Under the combined influence of jet impact and two-dimensional stress loading, the rock-breaking volume decreases, whereas the Fcdd value increases within a certain range. Three-dimensional stress loading significantly reduces the extent of rock fragmentation and damage, with both rock-breaking volume and Fcdd value decreasing exponentially as stress loading increases. Surface rock elements undergo instantaneous brittle failure, while deeper elements experience cumulative plastic damage. Stress loading has minimal impact on surface rock due to the extremely high water-hammer pressure but prolongs the initiation and accumulation of rock damage. Under water jet impact, the rock sequentially forms an erosion hole, fracture zone, plastic damage zone, elastic zone, and undamaged zone. Fragmentation and damage are more severe in the direction of greater stress loading, resulting in a larger fragmentation range. These findings could provide valuable insights for optimizing high-pressure water jet technology to efficiently break loaded rock in stress-endowed environments.